THE APPLICATION OF THE MODEL OF LEARNING PROCESS OF TEAM ASSISTED INDIVIDUALIZATION (TAI) CONCERNING TO THE ACTIVITIES OF STUDYING AND MASTERY OF THE CONCEPT OF THE STUDENT ON THE SUBJECT OF HUMAN ROLE IN EQUILIBRIUM OF ECOSYSTEM - wahyu wahyu; Tri Jalmo; Pramudiyanti Pramudiyanti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The result of observation and interview with biology teacher in class X of SMAN 1 Pagar Dewa, were found out the output of students have already lowered. This is caused by teachers that using inappropriate learning model. This research aim to understand of activity progress of study also mastery of concept the student by means of application of model learning process of TAI. This study is experimental kuasi with pretest, posttest design of group non-equivalent. The sample of research are students of class X5 and X6 that were chosen by cluster random sampling. The result of study shown that the student activity in every aspects were observed in the experiment class has already increased. The aspect of question has grade 87,5%, the aspect of answer the question is 90,28%, and the aspect to express of ides is 84,72%. Mastery of the concept also increasing, on the average of grades pretest 45, the grades of posttest is 67 and   N-gain is 0,39. In short, learning process by using model of TAI may increasing the activities of studying and mastery of the concept of student. Key words : TAI, activities of studying and mastery of the concept of student.